Contribution to the Tb-doped AlNxOy:H/c-Si(p) interface study using Surface Photovoltage (SPV) techniques for potential photovoltaic applications - Dulanto Carbajal, Jorge Alejandro (Pontificia Universidad Católica del Perú, 2023)
Hydrogenated Aluminum Oxynitride (AlNxOy:H) is a versatile material for the surface passivation of crystalline silicon (c-Si). The capability of having positive or negative fixed charges makes AlNxOy:H a suitable material for surface passivation of both n-type and p-type c-Si. Terbium (Tb) implemented in thin films is known for its potential for downshifting light. This work studies the electronic properties of the Tb-doped AlNxOy:H/cSi(p) interface. The studied samples’ layers were deposited by reactive direct current (DC) sputtering with different hydrogen flows and then annealed. Due to high leakage currents and high defect densities, the electronic properties of the Tb-doped AlNxOy:H layers could not be analyzed conclusively using standard techniques such as high-frequency capacitance-voltage (HF-CV) or quasi-steady-state photoconductance (QSSPC) measurements, respectively. As an alternative, the non-contact Surface Photovoltage (SPV) characterization technique enabled a profound investigation of the electronic features of the Tb-doped AlNxOy:H/c-Si (p) interface. Both modulated SPV and transient SPV measurements are performed. The capabilities of the SPV measurements make this technique unique and very effective in observing and measuring critical passivation properties of the Tb-doped AlNxOy:H samples. Particularly the transient SPV of the Tb-doped AlNxOy:H samples enabled the observation of different optical transitions (band to band, band to defect, defect to band) and carrier transport mechanisms between the Si surface and the Tb-doped AlNxOy:H. The changes in relaxation times among Tb-doped AlNxOy:H samples are noticeable due to spatial separation among defects (tunneling). This study uses complementary measurements like X-ray reflectometry (XRR), Photoluminescence (PL) and Fourier-transform infrared spectroscopy (FTIR) to obtain valuable information about the AlNxOy:H layer and the AlNxOy:H/c-Si(p) interface that validates the SPV results and observations. In the c-Si, through SPV, we observed strong accumulation with passivation of boron acceptors and the generation of defects near the interface. When the hydrogen flow was increased, the net negative charge in the Tbdoped AlNxOy:H layer decreased, and the surface photovoltage signals associated with defects increased. Transients SPV at higher hydrogen flows decayed faster, and hopping transport via an exponential distribution of trap states in energy replaced trap-limited relaxation of charge carriers separated in space. The particular conditions that these AlNxOy:H samples have, make transient SPV spectroscopy a unique and reliable technique to observe the electronic properties of the AlNxOy:H/c-Si(p) interface.

El oxinitruro de aluminio hidrogenado (AlNxOy:H) es un material versátil para la pasivación superficial del silicio cristalino (c-Si). La capacidad de tener cargas fijas positivas o negativas hace del AlNxOy:H un material adecuado para la pasivación superficial de c-Si tanto de tipo n como de tipo p. El terbio (Tb) implementado en láminas delgadas es conocido por su potencial para desviar la luz hacia abajo. En este trabajo se estudian las propiedades electrónicas de la interfase (AlNxOy:H)/c-Si (p) dopada con Tb. Las capas de las muestras estudiadas fueron depositadas mediante sputtering reactivo DC con diferentes flujos de hidrógeno y posteriormente recocidas. Debido a las elevadas corrientes de fuga y a las altas densidades de defectos, las propiedades electrónicas de las capas de AlNxOy:H dopadas con Tb no pudieron analizarse de forma concluyente utilizando técnicas estándar como las medidas de capacitanciavoltaje de alta frecuencia (HF-CV) o de fotoconductancia en estado cuasi estable (QSSPC), respectivamente. Como alternativa, la técnica de caracterización de fotovoltaje superficial (SPV) sin contacto permitió investigar en profundidad las características electrónicas de la interfaz AlNxOy:H/c-Si (p) dopada con Tb. Se realizan tanto medidas de SPV modulado como de SPV transitorio. Las capacidades de las medidas de SPV hacen que esta técnica sea única y muy eficaz para observar y medir las propiedades críticas de pasivación de las muestras de AlNxOy:H dopadas con Tb. En particular, la SPV transitoria de las muestras de AlNxOy:H dopadas con Tb permitió observar diferentes transiciones ópticas (banda a banda, banda a defecto, defecto a banda) y mecanismos de transporte de portadores entre la superficie de Si y el AlNxOy:H dopado con Tb. Los cambios en los tiempos de relajación entre las muestras de AlNxOy:H dopadas con Tb son apreciables debido a la separación espacial entre defectos (tunelización). Este estudio utiliza medidas complementarias como XRR, PL y FTIR para obtener información valiosa sobre la capa de AlNxOy:H y la interfase AlNxOy:H/c-Si (p) que valida los resultados y observaciones del SPV. En el c-Si, mediante SPV, observamos una fuerte acumulación con pasivación de aceptores de boro y la generación de defectos cerca de la interfaz. Al aumentar los flujos de hidrógeno, disminuyó la carga negativa neta en la capa de AlNxOy:H dopada con Tb, y aumentaron las señales de fotovoltaje superficial asociadas a los defectos. Los transitorios SPV a mayores flujos de hidrógeno decaían más rápidamente, y el transporte por saltos a través de una distribución exponencial de estados trampa en energía sustituía a la relajación limitada por trampas de portadores de carga separados en el espacio. Las condiciones particulares que presentan estas muestras de AlNxOy:H hacen de la espectroscopia SPV transitoria una técnica única y fiable para observar las propiedades electrónicas de la interfase AlNxOy:H/c-Si(p).
Keywords: Celdas solares--Silicio; Circuitos integrados--Pasivación; https://purl.org/pe-repo/ocde/ford#1.03.00